2020
DOI: 10.1007/s00382-020-05471-4
|View full text |Cite
|
Sign up to set email alerts
|

What causes the spread of model projections of ocean dynamic sea-level change in response to greenhouse gas forcing?

Abstract: Sea levels of different atmosphere–ocean general circulation models (AOGCMs) respond to climate change forcing in different ways, representing a crucial uncertainty in climate change research. We isolate the role of the ocean dynamics in setting the spatial pattern of dynamic sea-level (ζ) change by forcing several AOGCMs with prescribed identical heat, momentum (wind) and freshwater flux perturbations. This method produces a ζ projection spread comparable in magnitude to the spread that results from greenhous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
39
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 85 publications
10
39
1
Order By: Relevance
“…All surface forcing perturbations are applied at the ocean surface, such that sea ice is not directly affected (Fig. 1, see also Couldrey et al 2021). However, there will be indirect effects on sea ice due to the changes of heat and freshwater in response to all the perturbations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All surface forcing perturbations are applied at the ocean surface, such that sea ice is not directly affected (Fig. 1, see also Couldrey et al 2021). However, there will be indirect effects on sea ice due to the changes of heat and freshwater in response to all the perturbations.…”
Section: Methodsmentioning
confidence: 99%
“…Gregory et al (2016) provide more details on FAFMIP and first results in terms of ensemble mean and spread of the total resulting sea level anomalies and the comparison to those resulting from individual forcing using low-resolution models. More recently, Couldrey et al (2021)showed that surface heat flux changes drive most of the sea level change pattern in the FAFMIP runs and that the spread between underlying Atmosphere-Ocean General Circulation Models (AOGCM) is caused largely by differences in their regional transport adjustment, which redistributes regional heat content differences that existed in the ocean prior to perturbation. However, the quantification of the mechanisms behind the simulated responses as a function of surface forcing agent remains unclear in previous publications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DOI 10.1175/JCLI-D-20-0603.1. Unauthenticated | Downloaded 12/13/21 02:57 AM UTC  Finally, the relevance of improving estimation of OHCA and providing full quantification of uncertainty is justified by the uses in a wide range of climate science, such as hindcast reanalyses assimilating ocean data (Storto et al 2019), ocean and/or climate model analyses investigating the mechanisms of ocean heat uptake (Couldrey et al 2020;Dias et al 2020a;Dias et al 2020b;Gregory 2000;Gregory et al 2016;Saenko et al 2021;Savita et al 2021), detection and attribution of changes to natural and anthropogenic drivers (e.g. Gleckler et al 2012), and in constraining model projections of climate and sea level change relevant for policyand decision-makers (Lyu et al 2021;Mimura 2007;Oppenheimer et al 2019).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…To produce the regional SLR of the sterodynamic contribution, we use the spatial patterns of ocean dynamic sea-level changes of the IPCC AR5 models. This relies on the assumption that the regional variability of sea-level sterodynamic projections is driven by the same mechanisms in Kopp et al (2014) and for the IPCC AR5, as suggested by Couldrey et al (2021).…”
Section: Sterodynamic Componentmentioning
confidence: 99%